Potential contribution of new particle formation to cloud condensation nuclei in Beijing - Yue, D. L.; Hu, M.; Zhang, R. Y.; ZJ Wu; H. Su; Wang, Z. B.; Peng, J. F.; He, L. Y.; Huang, X. F.; Gong, Y. G.; Wiedensohler, A. (Atmospheric Environment, 2011)
New particle formation (NPF) events have been recognized as an important process contributing to the cloud condensation nuclei (CCN) formation. In this study, measurement of NPF and predicted number concentrations of CCN using kappa-Kohler theory were analyzed to assess the contribution of NPF to possible CCN. The particle growth rates of NPF events were categorized to two types: sulfur-rich (condensation and neutralization of sulfuric acid dominating net growth rate) and sulfur-poor cases. The growth rates for the sulfur-poor events were about 80% larger than those of the sulfur-rich cases on average. NPF events increased the CCN number concentrations by 0.4-6 times in the megacity area of Beijing. The enhancement ratios (the ratio of CCN number concentrations when obvious particle growth ended to that when it started during NPF events) were high for large supersaturation (S). For example, it was about 30-50% higher under S = 0.86% than under S = 0.07%. The enhancement ratios exhibited similar seasonal variation as the growth rates with a larger value in summer than other seasons, which suggested that growth rate was a key factor in the conversion of NPF to possible CCN. The enhancement ratios were higher during the sulfur-poor NPF events with larger growth rates mainly contributed by organic species, indicating that organic species were the dominant chemical contributor in facilitating the conversion of newly formed particles to possible CCN in the Beijing Megacity. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: activity; aerosol-particles; atmospheric; ccn; cloud condensation nuclei; Environmental Sciences & Ecology; global ccn; hygroscopic growth; mega-city; Meteorology & Atmospheric Sciences; nanoparticles; new particle formation; nucleation; number concentration; particle growth; pearl river-delta; size-resolved measurements; sulfuric-acid